Management interventions in indigenous bull to reduce age at first semen donation (Indian Journal of Animal Production and Management, 2024)
To achieve lifetime more semen productivity, one of the critical aim of breeding centers is to make sexual  maturity at early age in bulls. Therefore, a study was planned one group as control (n=5: applied only bull  nose ring, handling by Nath (halter), two hour exercise once in a week, different bull handler and semen  collection at 08.30 AM) and another group as treatment (n=5: applied halter along with bull nose ring,  handling by the halter, managed by same worker, two-hour exercise daily, semen collection at 06.30 AM)  to reduce the age at first semen donation through management inputs. Sexual behavior and semen quality  data of the two groups were analyzed by T-test. All the bulls (100%) in the treatment group started donating  semen by on an average 21.3 months, whereas only 60% bulls in control group donated semen on an  average 34.6 months. The results revealed that in the treatment group, the sexual behaviour improved  significantly (p
Keywords: Age at first semen donation; Exercise; Management input; Sahiwal bull; Sexual behaviour